Linking biophysical models with LiDAR-based vegetation mapping to evaluate thermal refugia at a landscape scale in the Kruger National Park - McKechnie, Andrew E. (University of Pretoria, 2024)
Mini Dissertation (MSc (Environmental Management))--University of Pretoria, 2024.